2017
DOI: 10.1002/med.21457
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of Structural Insights of Xanthine and Aldehyde Oxidases: An Overview of their Inhibitors and Role in Various Diseases

Abstract: Almost all drug molecules become the substrates for oxidoreductase enzymes, get metabolized into more hydrophilic products and eliminated from the body. These metabolites sometime may be more potent, active, inactive, or toxic in nature compared to parent molecule. Xanthine oxidoreductase and aldehyde oxidase belong to molybdenum containing family and are well characterized for their structures and functions, in particular to their ability to oxidize/hydroxylate the xenobiotics. Their upregulated clinical leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 241 publications
(459 reference statements)
0
80
0
3
Order By: Relevance
“…Schematic presentation of uric acid production. (Adopted from Kumar et al, with permission copy right 2017 Wiley) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Uric Acid (Ua): Production and Eliminationmentioning
confidence: 99%
“…Schematic presentation of uric acid production. (Adopted from Kumar et al, with permission copy right 2017 Wiley) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Uric Acid (Ua): Production and Eliminationmentioning
confidence: 99%
“…It has been reported that XOD inhibitors act as antioxidants to decrease ROS and prevent oxidative stress (Kumar et al, 2018;Lin et al, 2015;Nile et al, 2018). Herein, SA was shown to inhibit the XOD enzyme and to have moderate O −‱ 2 scavenging activity and a strong DPPH radical scavenging activity.…”
Section: Discussionmentioning
confidence: 88%
“…LXOD plays an important role in the pathophysiology of HUA and gout (Kumar et al, 2018). The XOD enzyme catalyzes hypoxanthine to xanthine and subsequently xanthine to UA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations